2022
DOI: 10.1093/bioinformatics/btac252
|View full text |Cite
|
Sign up to set email alerts
|

A LASSO-based approach to sample sites for phylogenetic tree search

Abstract: Motivation In recent years, full-genome sequences have become increasingly available and as a result many modern phylogenetic analyses are based on very long sequences, often with over 100 000 sites. Phylogenetic reconstructions of large-scale alignments are challenging for likelihood-based phylogenetic inference programs and usually require using a powerful computer cluster. Current tools for alignment trimming prior to phylogenetic analysis do not promise a significant reduction in the alig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…For this type of data with low homoplasy, bootstrap supports are strongly correlated with branch lengths (Felsenstein 1985). This confirms recent results on the predictability of branch supports by machine learning (Wiegert et al 2024; Ecker et al 2024). However, the usefulness of the bootstrap remains, especially for short branches corresponding to 1 or 2 mutations, where the signal can be conflicting and blurred by the homoplasy of the data, even if it is low (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…For this type of data with low homoplasy, bootstrap supports are strongly correlated with branch lengths (Felsenstein 1985). This confirms recent results on the predictability of branch supports by machine learning (Wiegert et al 2024; Ecker et al 2024). However, the usefulness of the bootstrap remains, especially for short branches corresponding to 1 or 2 mutations, where the signal can be conflicting and blurred by the homoplasy of the data, even if it is low (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, machine-learning algorithms were successfully applied in phylogenetic research, contributing to both runtime efficiency and enhanced inference accuracy. Noteworthy applications include their utilization in model selection tasks ( Abadi et al 2020 , Burgstaller-Muehlbacher et al 2023 ), inferring phylogenetic trees ( Suvorov et al 2020 ), ranking candidate trees during a tree-search ( Azouri et al 2021 ), identification of key genomic loci for elucidating a phylogenetic hypothesis ( Kumar and Sharma 2021 ), sampling of MSA positions to reduce tree-search running time ( Ecker et al 2022 ), and estimating the difficulty of the MSA ( Haag et al 2022 ). In this study, we have demonstrated the effectiveness of machine-learning algorithms for branch support estimation, a task traditionally relying on standard statistical tests.…”
Section: Discussionmentioning
confidence: 99%